The Effect of Fiscal Policy and Foreign Direct Investment on Regional Economy in Indonesia - Basuki, Agus Tri; Purwaningsih, Yunastiti; Soesilo, Albertus Maqnus; Mulyanto, Mulyanto (Jurnal Ekonomi & Studi Pembangunan, 2020)
The purpose of this study was to analyze the influence of the poor population, government spending and foreign investment on regional economic growth in 20 provinces and divided into 2 regions, then compare the effectiveness of fiscal policies in the 2 regions. The paper utilizes the fixedâ€effects and randomâ€effects techniques to estimate the panel regressions. The results showed that the right fiscal policy could increase economic growth in both the western and eastern regions of Indonesia. For the western region, revenue sharing is less effective than the eastern region in increasing economic growth, but conversely government spending on education, health and marine in the western region is more effective than the eastern region in increasing economic growth.